Lianhua Qingwen prescription for Coronavirus disease 2019 (COVID-19) treatment: Advances and prospects (2020)
Background: An outbreak of Coronavirus Disease 2019 (COVID-19) which was infected by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is still spreading and has led to unprecedented health emergency over the world. Though no specific drug has been developed so far, emerging agents have been confirmed effective or potentially beneficial to restrain it. Lianhua Qingwen (LHQW) is a commonly used Chinese medical preparation to treat viral influenza, including in the fight against SARS in 2002–2003 in China. Recent data also showed that LHQW played a vigorous role in COVID-19 treatment. Purpose: This review will elucidate the pre-clinical and clinical evidence of LHQW in lung protection and antiviral activities, and provide timely data delivery for the exploration of effective treatment strategies in the therapy of COVID-19. Study design and method: The research data were obtained from the academic databases (up to August 8, 2020) including Pubmed, CNKI and Web of Science, on ethnobotany and ethno medicines. The search keywords for screening the literature information were “virus”, “COVID-19”, or “SARS-CoV-2”, and “Lianhua Qingwen”. The documents were filtered and summarized for final evaluation. Results: The collected evidence demonstrated that LHQW exhibited benefits against COVID-19. Impressively, LHQW in conjunction with conventional treatment could significantly improve COVID-19 patients as a synergetic strategy. The mechanisms were mainly involved the antiviral activity, and regulation of inflammation response as well as immune function. Conclusion: Although the data were far from adequate, the latest advances had shown the benefits of LHQW in COVID-19, especially in combination with other antiviral drugs. This review provides comprehensive evidence of LHQW as a complementary strategy for treating COVID-19. Nevertheless, imperious researches should be conducted to clarify the unconfirmed effects, regulatory mechanisms and adverse reactions of LHQW in treating COVID-19 by means of well designed randomized controlled trials.